Eksplorasi Model Hannfin and Peck Sebagai Alternatif Pendekatan Pembelajaran Inovatif pada Mata Pelajaran PAI di Sekolah Dasar - Shobarina, Gina Nurul; Tarsono, Tarsono; Nugraha, Mulyawan Safwandy (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This research aims to analyze the exploration of the Hannafin and Peck model as an alternative innovative learning approach in PAI subjects. The Hannafin and Peck model is a learning design model that consists of three phases. 1) requirements analysis phase, 2) design phase, 3) development and implementation phase. This model is product-oriented, usually learning mesdia such as learning videos, learning multimedia, or modules. This research uses a qualitative approach with a 4D development model (define, design, develop, and disseminate) aimed at producing or perfecting certain products, and testing the effectiveness of these products. The result obtained show that this model is considered good and effective if implemented as an alternative innovative learning approach, because it is an update to existing learning models. However, the expected results have not yet reached a perfect level because of the various challenges and phase that must be passed. The products produced are in the form of modules (printed teaching materials), learning videos, and students making the Palestinian flag as a form of empathy and sympathy for Muslim countries. Apart from that, the strategy used is picture and picture as a learning model for prayer movement teaching materials. Keywords: Learning Model; Hannfin and Peck; Innovative Learning